2008
DOI: 10.1002/mnfr.200800054
|View full text |Cite
|
Sign up to set email alerts
|

Dietary procyanidins lower triglyceride levels signaling through the nuclear receptor small heterodimer partner

Abstract: Hypertriglyceridemia is an independent risk factor in the development of cardiovascular diseases, and we have previously reported that oral administration of a grape seed procyanidin extract (GSPE) drastically decreases plasma levels of triglycerides (TG) and apolipoprotein B (ApoB) in normolipidemic rats, with a concomitant induction in the hepatic expression of the nuclear receptor small heterodimer partner (NR0B2/SHP). Our objective in this study was to elucidate whether SHP is the mediator of the reduction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
83
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 68 publications
(92 citation statements)
references
References 53 publications
(43 reference statements)
8
83
1
Order By: Relevance
“…The main objective of this work was to identify the molecule(s) responsible for the bioactivity of a grape seed procyanidin extract that act in vivo as (a) an antihyperglycemic (Pinent et al, 2004), (b) an antiatherogenic (del Bas et al, 2005Bas et al, , 2008 and (c) an antiinflammatory (Terra et al, 2008) product. To meet this objective, three cell lines in which GSPE has been identified as being highly active, namely adipocytes (Pinent et al, 2005;Pinent, Bladé, Salvadó, Arola, & Ardévol, 2005a, 2005b, hepatocytes (del Bas et al, 2005;Puiggròs et al, 2005), and macrophage cells (Terra et al, 2007) were used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main objective of this work was to identify the molecule(s) responsible for the bioactivity of a grape seed procyanidin extract that act in vivo as (a) an antihyperglycemic (Pinent et al, 2004), (b) an antiatherogenic (del Bas et al, 2005Bas et al, , 2008 and (c) an antiinflammatory (Terra et al, 2008) product. To meet this objective, three cell lines in which GSPE has been identified as being highly active, namely adipocytes (Pinent et al, 2005;Pinent, Bladé, Salvadó, Arola, & Ardévol, 2005a, 2005b, hepatocytes (del Bas et al, 2005;Puiggròs et al, 2005), and macrophage cells (Terra et al, 2007) were used.…”
Section: Resultsmentioning
confidence: 99%
“…Values were corrected per milligram of protein, determined using the Bradford methodology (Bradford, 1976). The medium was collected after 24 h treatment and apolipoprotein B was detected as described in del Bas et al (2008).…”
Section: Cell Culture and Measurementsmentioning
confidence: 99%
“…34) Moreover, a grape seed procyanidin extract upregulated CPT under the regulation of the nuclear receptor small heterodimer partner in mouse liver. 35) It is therefore likely that the proanthocyanidins from the BBL hot water extract were also actively involved in lipolysis. A previous study has demonstrated that BBL extracts contained a large amount of oligomeric and polymeric anthocyanidins.…”
Section: )mentioning
confidence: 99%
“…In HepG2 cells, grape procyanidins require the activity of SHP to reduce secretion of TG whereas, in contrast, they reduce the secretion of ApoB in a SHP-independent way [16]. Also, SHP mediates the hypotriglyceridemic effect of grape procyanidins in wild-type mouse in the postprandial state, which is accompanied by the downregulation of hepatic expression of transcription factor SREBP1 [16], a master mediator for insulin/glucose signaling to lipogenesis (reviewed in [17, 18]).…”
Section: Introductionmentioning
confidence: 99%